2022
DOI: 10.1002/acr.24770
|View full text |Cite
|
Sign up to set email alerts
|

Confirming Prior and Identifying Novel Correlates of Acute Calcium Pyrophosphate Crystal Arthritis

Abstract: Objective. To investigate previously identified and novel correlates of acute calcium pyrophosphate (CPP) crystal arthritis among well-characterized cases.Methods. In this case-control study, we identified cases of acute CPP crystal arthritis using a validated algorithm (positive predictive value 81%) applied in the Partners HealthCare electronic health record (EHR). Cases were matched to general patient controls on the year of first EHR encounter and index date. Prespecified potential correlates included sex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…We performed a matched cohort study using EHR data from the Mass General Brigham Research Patient Data Repository (RPDR), 1991–2017. This repository includes data for >5 million patients at Brigham and Women’s Hospital, Massachusetts General Hospital and affiliated sites 15. RPDR data include demographics, body mass index, diagnosis codes, procedure codes and prescription medications from inpatient and outpatient encounters at Mass General Brigham facilities.…”
Section: Methodsmentioning
confidence: 99%
“…We performed a matched cohort study using EHR data from the Mass General Brigham Research Patient Data Repository (RPDR), 1991–2017. This repository includes data for >5 million patients at Brigham and Women’s Hospital, Massachusetts General Hospital and affiliated sites 15. RPDR data include demographics, body mass index, diagnosis codes, procedure codes and prescription medications from inpatient and outpatient encounters at Mass General Brigham facilities.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of CPPD reported depends much on the joints studied. In Italy, CC was among the five most prevalent musculoskeletal conditions observed with a prevalence of 0.42% [12]. In other surveys, CC was detected in 7-10% of knees together with hands, wrists, hips, and the symphysis pubis, respectively [14][15][16][17][18].…”
mentioning
confidence: 92%
“…The epidemiology of manifestations and phenotypes of CPPD is in part still controversial [9,10]. Women were more frequently affected than men in two studies [11,12]. However, in a recent study, for the first time higher odds for acute CPPD among males have been reported [13].…”
mentioning
confidence: 99%